2021
DOI: 10.18051/univmed.2021.v40.22-28
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index as the most influential factor of high-sensitivity C-reactive protein in non-diabetic adults

Abstract: BACKGROUND<br />High-sensitivity C-reactive protein (hsCRP) has been widely accepted as a predictor of future cardiovascular risk that reflects a microinflammatory state. Obesity linked to microinflammation increases the prevalence of metabolic disorders and cardiovascular diseases. This study aimed to determine the association between several obesity indices namely body mass index (BMI), waist circumference (WC), body fat percentage (fat), and visceral fat (VF) with hsCRP in non-diabetic adults. <br … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…In our study, there was a significant correlation between body mass index (p = 0.001; r = 0.526) and serum Hs-CRP levels in overweight and obese individuals. This is in line with the research by Mulyamin et al (2021) which stated that body mass index is a factor that affects serum Hs-CRP levels in overweight and obese individuals and in non-diabetic adults [2][11] [20]. Research by Rattu et al [21] in Manado also found a significant positive relationship between body mass index and serum Hs-CRP levels in obese students and no significant relationship between BMI and Hs-CRP levels in non-obese students [21][22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, there was a significant correlation between body mass index (p = 0.001; r = 0.526) and serum Hs-CRP levels in overweight and obese individuals. This is in line with the research by Mulyamin et al (2021) which stated that body mass index is a factor that affects serum Hs-CRP levels in overweight and obese individuals and in non-diabetic adults [2][11] [20]. Research by Rattu et al [21] in Manado also found a significant positive relationship between body mass index and serum Hs-CRP levels in obese students and no significant relationship between BMI and Hs-CRP levels in non-obese students [21][22].…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with a previous study which found that waist circumference is significantly related to the increase in serum Hs-CRP levels in overweight and obese patients [11]. The anthropometric parameters significantly associated with Hs-CRP are the body mass index and waist circumference [20]. Waist circumference is a parameter of abdominal obesity with a waist circumference > 80 cm for women and > 90 cm for men indicating abdominal obesity or central obesity.…”
Section: Discussionsupporting
confidence: 92%